Frequency-specific effects of stimulation of the subthalamic area in treated Parkinson's disease patients. - Kühn, A; Fogelson, N; Limousin, P; Hariz, M; Kupsch, A; Brown, P (2009)
It has been hypothesized that too much synchronization in the beta band in basal ganglia-cortical circuits can contribute to bradykinesia and too little can contribute to hyperkinesia. The former has been supported by experiments in patients with Parkinson's disease and chronic implantation of the subthalamic area for deep brain stimulation. Stimulation at 20 Hz in this region slows voluntary tapping when performed in patients withdrawn from their usual antiparkinsonian medication. Here, we show the converse, that stimulation of the same region at 20 Hz in patients treated with levodopa decreases the interval between taps by 8.1+/-1.8% and makes tapping more regular. We suggest that this effect is mediated through an amelioration of levodopa-induced dyskinesias during stimulation.